A pilot-scale floating closed culture system for the multicellular cyanobacterium Arthrospira platensis NIES-39 - Toyoshima, Masakazu; Aikawa, Shimpei; Yamagishi, Takahiro; Kondo, Akihiko; Kawai, Hiroshi (Journal of applied phycology, 2015)
Microalgae are considered to be efficient bio-resources for biofuels and bio-based chemicals because they generally have high productivity. The filamentous cyanobacterium Arthrospira ( Spirulina ) platensis has been widely used for food, feed, and nutrient supplements and is usually cultivated in open ponds. In order to extend the surface area for growing this alga, we designed a pilot-scale floating closed culture system for cultivating A. platensis on open water and compared the growth and quality of the alga harvested at both subtropical and temperate regions. The biomass productivity of A. platensis NIES-39 was ca. 9 g dry biomass m −2 day −1 in summer at Awaji Island (warm temperature region) and ca. 10 and 6 g dry biomass m −2 day −1 in autumn and winter, respectively, at Ishigaki Island, (subtropical region) in Japan. If seawater can be used for culture media, culture cost can be reduced; therefore, we examined the influence of seawater salt concentrations on the growth of A. platensis NIES-39. Growth rates of A. platensis NIES-39 in diluted seawater with enrichment of 2.5 g L −1 NaNO3, 0.01 g L −1 FeSO 4 ·7H 2 O, and 0.08 g L −1 Na 2 EDTA were considerably lower than SOT medium, but the biomass productivity (dry weight) was comparable to SOT medium. This is explained by the heavier cell weight of the alga grown in modified seawater media compared to the alga grown in SOT medium. Furthermore, A. platensis grown in modified seawater-based medium exhibited self-flocculation and had more loosely coiled trichomes.